2015
DOI: 10.1093/rfs/hhv049
|View full text |Cite
|
Sign up to set email alerts
|

Durable Goods, Inflation Risk, and Equilibrium Asset Prices

Abstract: High inflation predicts a decline in future real consumption and equity cashflows, which is significantly stronger for durable than for non-durable goods. This suggests that durables is an important channel through which inflation affects long-term economic growth and asset prices. We derive and estimate an equilibrium two-good nominal economy with recursive utility over durable and nondurable consumption and persistent variations in real expected growth rates and expected inflation. Our model can account for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 73 publications
(108 reference statements)
0
20
0
Order By: Relevance
“…Eraker et al . () extend the homoskedastic model by durable goods and inflation. Based on the Bayesian MCMC method, they estimate an EIS of 2.39.…”
Section: Consumers' Preferences and The Eismentioning
confidence: 99%
“…Eraker et al . () extend the homoskedastic model by durable goods and inflation. Based on the Bayesian MCMC method, they estimate an EIS of 2.39.…”
Section: Consumers' Preferences and The Eismentioning
confidence: 99%
“…Piazzesi and Schneider (2006), Hasseltoft (2012), Bansal and Shaliastovich (2013) and others who provide empirical evidence for this channel for a single non-durable consumption good. Recently, Eraker, Shaliastovich, and Wang (2014) extended the literature in the context of durable consumption as well. They also showed that the negative correlation between inflation and consumption is highly pronounced when consumption goods exhibit durability.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the nominal channel as described by Bansal and Shaliastovich (2013) and Eraker, Shaliastovich, and Wang (2016), it is useful to consider the following Fisher-type equation:…”
Section: Model Solutionmentioning
confidence: 99%